PSYCHOSOCIAL RESOURCES AND EMOTIONS IN WOMEN WITH HIV-RELATED COGNITIVE IMPAIRMENT. (11th November 2018) - Halpin, S N; Ge, L; Christina Mehta, C; Gustafson, D; Robertson, K; Vance, D; Ofotokun, I
Abstract: Persons aging with HIV are at risk for cognitive and emotional changes--yet, emotional changes are ill-defined. A previous study identified psychosocial resources (informal caregiver support (ICS), formal caregiver support (FCS), control, and coping) that may predict emotions (i.e., anger, anxiety, apathy, depression, and fear) in persons with Alzheimer's disease (socio-emotional adaptation (SEA) theory). The current study sought to test this theory in 399 HIV-positive participants with cognitive impairment from the Women's Interagency HIV Study (WIHS). Most participants were older (median age= 51 years), African American (77%); and had a high school education or less (74%). Logistic-regression models resulted in partial replication of the SEA theory. Anger was associated with less coping, ICS, and FCS (all p<0.05); anxiety with lower ICS, FCS, control, and coping (all p<0.05); and a lack of emotional comorbidities with better ICS and coping (both p<0.05). Results may help target treatment and patient management plans.